2020
DOI: 10.3389/fmicb.2020.00196
|View full text |Cite
|
Sign up to set email alerts
|

Radezolid Is More Effective Than Linezolid Against Planktonic Cells and Inhibits Enterococcus faecalis Biofilm Formation

Abstract: The aim of this study was to compare the effects of radezolid and linezolid on planktonic and biofilm cells of Enterococcus faecalis. A total of 302 E. faecalis clinical isolates were collected, and the minimum inhibitory concentrations (MICs) of radezolid and linezolid were determined by the agar dilution method. Changes in the transcriptome of a highlevel, in vitro-induced linezolid-resistant isolate were assessed by RNA sequencing and RT-qPCR, and the roles of efflux pump-related genes were confirmed by ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The efflux pump may be involved in the resistance to tedizolid and radezolid for E. faecalis isolates. However, we analyzed the effects of linezolid, tedizolid, and radzolide on the expression of efflux pump gene ( OG1RF12220, OG1RF10126 , and OG1RF1049 ) referring to Zheng et al, 26 our results showed it did not influence these efflux pumps. The role of other efflux pump would also be studied in our future studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The efflux pump may be involved in the resistance to tedizolid and radezolid for E. faecalis isolates. However, we analyzed the effects of linezolid, tedizolid, and radzolide on the expression of efflux pump gene ( OG1RF12220, OG1RF10126 , and OG1RF1049 ) referring to Zheng et al, 26 our results showed it did not influence these efflux pumps. The role of other efflux pump would also be studied in our future studies.…”
Section: Discussionmentioning
confidence: 93%
“…The expression levels of E. faecalis (FC2234 FC2559 FC1728 FC1037 FC2398 FC2471) efflux pump-related genes ( OG1RF12220, OG1RF10126 , and OG1RF10495 ) were determined by RT-qPCR based on published reports. 26 Real-time qPCR was performed using the 7500 RTPCR System (Thermo Fisher Scientific, Marsiling, Singapore) equipped with the SYBRTM Green RT-PCR Kit (TOYOBO, Osaka, Japan). The primers used for qRT-PCR are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[144][145] In a recent study, Qu and colleagues investigated the effect of radezolid on planktonic and biofilm cells of Enterococcus faecalis and compared the results with linezolid. [146] The authors found a significantly greater effect of radezolid on planktonic E. faecalis cells than linezolid. The biofilm biomass was evaluated by crystal violet staining and the adherent cells were quantified according to CFU numbers.…”
Section: Modification Of the Morpholine Unit: Aryl Ring Systems With ...mentioning
confidence: 95%
“…e antibiotics Tazobactam/Ceftolozane [29], Radezolid [30], Cefatrizine [31], Tertbutyldimethylsilylspiroaminooxathioledioxide (TSAO) [32], and the Carboxyamidotriazole (CAI) [33] are examples of pharmaceutical drugs containing 1,2,3-triazoles scaffold (Scheme 9). We discuss the synthesis process of these pharmaceutical medicines in this study.…”
Section: Synthesis and Structure Of 123-triazole-based Marketedmentioning
confidence: 99%